2015
DOI: 10.1039/c4ra11399c
|View full text |Cite
|
Sign up to set email alerts
|

Development of a novel voltammetric sensor for the determination of methamphetamine in biological samples on the pretreated pencil graphite electrode

Abstract: We developed a simple and reliable sensor for the determination of methamphetamine without expensive and time-consuming pretreatments using PPGE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(25 citation statements)
references
References 39 publications
0
24
0
1
Order By: Relevance
“…The LOD compares favourably with that obtained using indirect electrochemistry with 1,2-naphthoquinone-4-sulfonate [ 16 ], and it is considerably higher than the LODs obtained using direct electrochemical methods [ 13 15 ], although all these methods use aqueous solution and not undiluted saliva. Use of microelectrodes should provide greater sensitivity of response, since increased mass transport of MAMP to the electrode should result in increased peak heights i.e.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…The LOD compares favourably with that obtained using indirect electrochemistry with 1,2-naphthoquinone-4-sulfonate [ 16 ], and it is considerably higher than the LODs obtained using direct electrochemical methods [ 13 15 ], although all these methods use aqueous solution and not undiluted saliva. Use of microelectrodes should provide greater sensitivity of response, since increased mass transport of MAMP to the electrode should result in increased peak heights i.e.…”
Section: Resultsmentioning
confidence: 88%
“…There are only a few reports of the electrochemical sensing of amphetamines, and there are no reports of the determination of amphetamines in undiluted saliva using disposable electrochemical sensors. Electrochemical sensing of methamphetamine by direct oxidation has been reported at a pretreated pencil graphite electrode [LOD 50 nM (7.5 ng/mL) in aqueous solution, response time >10 min] [ 13 ], at a self-assembled boron-doped diamond electrode [LOD 50 nM (7.5 ng/mL) in aqueous solution, response time not given] [ 14 ], and in alkaline solution using a gold nanoparticle-multiwalled carbon nanotube modified screen printed electrode [LOD 0.3 nM (0.05 ng/mL), response time not given] [ 15 ]. The indirect electrochemical detection of amphetamine in saliva has been reported using 1,2-naphthoquinone-4-sulfonate at an edge plane pyrolytic graphite electrode [LOD 41 μM (6.2 μg/mL) in aqueous solution, response time not given] [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…SEP/MWCNTs/pPGE demonstrates a notable increase in the peak current value compared to the other electrodes (Figure ). The SEP/MWCNTs/pPGE composite electrode may be attributed to the fact that the pretreatment and modifiers added caused the surface area of the pencil graphite electrode to increase . The active surface areas of five electrodes were calculated in 5.0 mM Fe(CN) 6 3−/4− in 0.1 M KCl using the Randles‐Sevcik equation .…”
Section: Resultsmentioning
confidence: 99%
“…It was shown that electrochemical pretreatment activates the electrode surface by modifying its surface and redox characteristics [ 2 , 21 , 57 , 106 ]. In comparison to nontreated PGE, the electrochemically pretreated PGE (ETPGE) presented improved electrocatalytic activity (e.g., for uric acid and ascorbic acid [ 2 ], methamphetamine [ 101 ], sulfide [ 192 ]), higher sensitivity (e.g., a 2–5 times higher sensitivity for monophenols [ 9 ] and a 40-fold increase of uric acid voltammetric signal [ 91 ]), higher selectivity by increasing the peaks separation [ 2 , 21 ], and better adsorption capacity of organic compounds [ 57 , 106 , 192 , 193 ]. This properties strongly depend on the activation conditions, that is, electrochemical procedure, electrolyte (type and concentration), applied potential or potential range [ 54 ], number of scans, and scan rate [ 21 , 54 , 106 ].…”
Section: Discussionmentioning
confidence: 99%
“…PGEs were pretreated potentiostatically by maintaining the electrode in an electrolyte for more than 30 s at a selected potential higher than 1.3 V [ 9 , 53 , 55 , 56 , 60 , 70 , 99 101 , 105 , 192 , 193 ] or by scanning the potential at a given scan rate, for a certain number of cycles within a large potential range [ 2 , 57 , 58 , 61 , 69 , 103 , 106 , 188 , 194 ]. Some papers report a comparison between the two mentioned activation procedures and depending on the electrochemical performances obtained for the investigated analyte one of them was selected; for example, chronoamperometric activation of PGE was used for alkylphenols [ 50 ] and tannic acid [ 51 ] analysis and cyclic voltammetric activation of PGE for dopamine [ 21 ] and bisphenol A [ 54 ] detection.…”
Section: Discussionmentioning
confidence: 99%